Beyond the virus: Ensuring continuity of care for people with diabetes during COVID-19. Issue 1 (February 2021) - Beran, David; Aebischer Perone, Sigiriya; Castellsague Perolini, Montserrat; Chappuis, François; Chopard, Pierre; Haller, Dagmar M.; Jacquerioz Bausch, Frédérique; Maisonneuve, Hubert; Perone, Nicolas; Gastaldi, Giacomo
Abstract: The current COVID-19 pandemic is a major concern for the diabetes community. A meta-analysis in China found that the proportions of people with COVID-19 and diabetes was 9.7% and that having diabetes resulted in a two-fold increased risk of having a severe case. Global guidance on confinement measures for the prevention of COVID-19 have a particular emphasis on vulnerable populations which include people with diabetes. These recommendations are coherent to avoid the spread of SARSCoV-2 infection, but are in contradiction with comprehensive diabetes care, which requires regular patient–provider interactions for patient education, prescriptions and possible management of complications or mental health. Moreover, confinement drives risk for unhealthy diets, decreased physical activity, mental health related concerns, in parallel to delayed care-seeking due to fear of contracting COVID-19. Another weakness in the current COVID-19 response is the focus on hospital care which overlooks the importance of Primary Care in guaranteeing continuity of care. Ensuring the availability of insulin, other medicines, self-monitoring and diagnostic tools is another challenge. These are all global concerns for the diabetes community, as well as for those suffering from other chronic conditions. Undoubtedly, the global priority is to contain the spread and impact of COVID-19. However, health systems still need to meet the needs of the entire population, including individuals with diabetes. Clear guidance for preparedness, crisis and post-crisis management of diabetes and chronic diseases during mass disruptions to health systems are lacking. Therefore, in parallel to the epidemic response efforts to ensure existing healthcare services keep running should be supported to avoid health consequences that might be worse than the epidemic itself. This includes targeted messaging for people with diabetes and vulnerable populations with regards to possible risk of infection as well as their disease-related management; continued support via telephone, video conferencing or even home visits; ensuring access to insulin and other medicines and supplies both nationally and individually; and most importantly, preparing for the future.